APPLICATIONS IN MACHINE TRANSLATION, SPEECH RECOGNITION, AND ARTIFICIAL INTELLIGENCE (International Conference on Economics, Finance, Banking and Management, 2025)
This paper explores the interdisciplinary applications of machine translation, speech recognition, and artificial intelligence (AI). It examines how linguistic theories, data-driven models, and deep learning techniques have transformed communication, education, and industry. The paper also discusses the challenges and ethical implications of integrating AI technologies in natural language processing (NLP) systems, emphasizing future directions for human–machine interaction.